EFFECT OF DIFFERENT WEED MANAGEMENT PRACTICES ON SOIL BACTERIAL POPULATION UNDER DIFFERENT CROPS - D. NONGMAITHEM; D. PAL (The Bioscan, 2012)
Field experiment was conducted at BCKV, West Bengal to study the effect of nine weed management practices on soil bacterial population in different crops (Sesame, Green gram and Black gram). The study revealed that at 7 DAS, the population of all the soil bacteria were found to reduce from their initial population in all the crops but were found to increase from 15 DAS till 30 DAS where the highest population of all the bacteria was found in black gram crop recording 33.37 CFU×104 g-1 of soil in aerobic non-symbiotic nitrogen fixing bacteria, 26.87 CFU×104 g-1 of soil in phosphate solubilising bacteria and 72.69 CFU×104 g-1 of soil in total bacteria. Among the weed management practices the population of soil bacteria were found to be lowest under chemical herbicide treatment W8-Quizalofop-p-ethyl @50g a.i ha-1 which recorded 13.50 CFU×104 g-1 of soil, 6.67 CFU×104 g-1 of soil and 31.94 CFU×104 g-1 of soil in aerobic non-symbiotic nitrogen fixing bacteria, phosphate solubilising bacteria and total bacteria respectively while hand weeding recorded maximum population at the final stage of observation with 42.50 CFU×104 g-1 of soil, 39.50 CFU×104 g-1 of soil and 99.00 CFU×104 g-1 of soil in aerobic non-symbiotic nitrogen fixing bacteria, phosphate solubilising bacteria and total bacteria respectively. Among the plant extracts (bio-herbicides), Ageratum conyzoides extract resulted in maximum population of different soil bacteria. It can, thus, be concluded that the conventional method of hand weeding results in multiplication of useful soil bacteria without hampering the population at all the stages of crop growth. In order to check the declining population under chemical herbicidal treatments, the use of such chemicals at lower doses accompanied by incorporation of hand weeding is to be recommended.